Pengembangan Media Pembelajaran Kartu Domino Modifikasi pada Mata Pelajaran Akidah Akhlak Kelas VII di MTS Yayasan Al- Hidayah Malili - Ariani; Hasbi; Bustanul Iman RN (Indonesian Journal of Islamic Educational Review, 2025)
This development research aims to determine the stages of development of modified domino card media in the subject of moral beliefs in class VII MTs Al-Hidayah Malili Foundation; to assess the validity of the modified domino card media in the subject of moral beliefs in class VII MTs Al-Hidayah Malili Foundation; to determine the level of practicality of modified domino card media in the class VII moral aqidah subject at MTs Al-Hidayah Malili Foundation.  This type of research is a type of R&D (Research and Development) research commonly called research and development. The model used in this research is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects in this research were 21 students in class VII MTs Al-Hidayah Malili Foundation for the 2023/2024 academic year. The results of this development research obtained the level of validity of the modified domino card media on the subject of moral beliefs and material on the attributes of Allah SWT. Categorized as very valid based on the average value of 93%. The level of practicality of the modified domino card learning media in moral beliefs is material on the characteristics of Allah SWT. Categorized as very practical based on the average teacher and student response questionnaire score, namely 85%.